Analisis peran guru dalam peningkatan akhlak siswa SMP Islam Bani Hasyim Singosari - Khairul, Riza Khairul (Maliki Interdisciplinary Journal, 2024)
The importance of instilling morals in children from an early age is carried out in their environment. At this time there are many problems occurring in society because there is no instilling morals in children, in the end quite a few young people today are caught in criminal cases such as theft, murder, therefore the National Commission on Child Human Rights was born which really regulates child protection. and the future of the child in his care. Returning to the initial context, the environment is the place where the child is forged and exposed to what will determine the child's character. So, therefore, schools must have non-formal moral learning in its application so that students can protect themselves from despicable actions in this era which are so harsh. Attack after attack, trial after trial for today's young people in the excitement of a sparkling world without knowing the importance of akhlakul kharimah. The most important role in the school in forming kharimah morals is that of a teacher, because teachers are public figures for students both at school and outside school. Therefore, there are teacher slogans that are used and imitated. If teachers cannot model good behavior to their students, then students will not get a good example of the importance of implementing morals.